PEMANFAATAN SAGU BARUK (Arenga Microcarpa) DENGAN UBI JALAR UNGU (Ipomoea Batatas) DALAM PEMBUATAN MIE BASAH - Cherly I.J. Lensun; Erny J.N Nurali; Tineke M. Langi; Jenny E.A. Kandou (Universitas Sam Ratulangi, 2013)
ABSTRACTCommonly, noodles aremade from sorghum flour. Recently, the developing of noodle procesing is become more various. Sweet potato, as a carbohydrate source, nowget a big attention from Indonesia government to be developed as a alternative food. The purposes of this research are to (1) to obtain the optimum concentration of corn starch and purple sweet potato flour in noodle processing ; (2) to analyzed the physical and sensory quality of the resulting noodles. The result shown that the addition of sago flour (25 %) mixedwith purple sweet potato flour (75%) is the most preferred by the panelists for color, taste and smell of a noodle produced. The nutrition content of noodles made from sago â€œbarukâ€ flour and sweet potato flour are: 0.63 to 1.49% protein,28.02 to 34.94% water, ash 2.02 to 8.76%, and water absorption 8 0.33 to 14, 41% in accordance with SNI.Keywords:Sago, Sweet Potato Purple, Noodle